Karakteristik dan Daya Terima Snack Bar dengan Substitusi Tepung Ubi Ungu (Ipomoea batatas (L.) Lam.) dan Penambahan Bubuk Spirulina platensis - Soma Aditya Putra; Annis Catur Adi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
The increasing exposure to free radicals due to modern lifestyles can trigger oxidative stress, highlighting the need for the development of food products containing bioactive compounds. Purple sweet potato (Ipomoea batatas L.) and Spirulina platensis are potential ingredients for the development of functional food products. This study aimed to analyze the sensory characteristics and acceptability of snack bars formulated with purple sweet potato flour substitution and the addition of Spirulina platensis powder. The study used three formulations, namely F0 (control), F2, and F3. Sensory evaluation was conducted using a five-point hedonic scale with 30 untrained panelists, assessing color, aroma, taste, aftertaste, and texture. Data were analyzed using the Friedman test followed by the Wilcoxon signed-rank test. The results showed that color, aroma, taste, and aftertaste were not significantly different among formulations (p > 0.05), while texture showed a significant difference (p < 0.05). Formula F2 had the highest overall acceptability compared to the other formulations. The results showed that color, aroma, taste, and aftertaste were not significantly different among formulations (p > 0.05), while texture showed a significant difference (p < 0.05). Formula F2 had the highest overall acceptability compared to the other formulations.